Pandemi As A Reason Force Majeure In Contract Procurement Of Goods / Government Services - Fitri Yanni Dewi Siregar (NOMOI Law Review, 2020)
Procurement of goods and services is an effort to obtain the desired goods and services by doing it on the basis of logical and systematic thinking (the system of thought), following applicable norms and ethics, based on standard procurement methods and processes.However, when a pandemic event occurs, many activities of every person and institution related to the procurement of goods / services become impeded.The occurrence of the Covid-19 pandemic required the state to prioritize the safety of the population, and therefore it was necessary to provide sufficient budget.This is what causes a